Hemodynamic response and pulse wave analysis after upper- and lower-body resistance exercise with and without blood flow restriction - Tai, Y. L.; Marshall, E. M.; Parks, J. C.; Kingsley, J. D. (European Journal of Sport Science, 2022)
Resistance exercise (RE) has been shown to elevate hemodynamics and pulse wave reflection. However, the effects of acute RE with blood flow restriction (BFR) on hemodynamics and pulse wave reflection are unclear. The purpose of this study was to evaluate the differences between upper- and lower-body RE with and without BFR on hemodynamics and pulse wave reflection. Twenty-three young resistance-trained individuals volunteered for the study. Hemodynamics and pulse wave reflection were assessed at rest, 10, 25, 40, and 55 minutes after either upper- or lower-body with or without BFR. The upper-body RE (URE) consisted of the latissimus dorsi pulldown and chest press; the lower-body RE (LRE) consisted of knee extension and knee flexion. The BFR condition consisted of four sets of 30, 15, 15, and 15 repetitions at 30% 1-repetition maximum (1RM) while the without BFR condition consisted of four sets of 8 repetitions at 70% 1RM. Heart rate, rate pressure product, and subendocardial viability ratio significantly (p<0.05) increased after all exercises. Brachial and aortic systolic blood pressure (BP) significantly (p<0.05) elevated after LRE while brachial and aortic diastolic BP significantly (p<0.05) reduced after URE. Augmentation pressure, augmentation index (AIx), AIx normalized at 75 bpm, and wasted left ventricular pressure energy significantly (p<0.05) increased after URE while transit time of reflected wave significantly (p<0.05) decreased after LRE. URE places greater stress on pulse wave reflection while LRE results in greater responses in BP. Regardless of URE or LRE, the cardiovascular responses between BFR and without BFR are similar.